Biochemical parameters of blood plasma of the male population living on the territory of the Aral Sea - Sabirov, Z.B.; Eshmagambetova, A.B.; Turlybekova, G.K.; Duzbayeva, N.M.; Mukasheva, M.A.; Onoshko, I.A. (Fundamental and Experimental Biology, 2020)
The Aral Sea ecological disaster zone affects the health status of the population living in this zone. Biochemical parameters are indicators of the metabolic functionality of the body. The article presents data about the biochemical parameters of blood plasma in the male population living in the ecological crisis zone of the Aral Sea region. It is shown that when determining the majority of indicators of biochemical analysis within the physiological norm, there is a significant percentage of people with deviations in these indicators. Such data make it possible to assume about the factors that can affect the entire population and have massive manifestations. Certainly, these factors, include the negative impact of the environment on public health. An increase in gamma — glutamyltransferase was found in 41 % of the subjects, an increase in cholesterol in 38 % and an increase in triglycerides in 34 %. In the inhabitants of the Aral Sea, a correlation was found between the biochemical parameters of blood serum from the dose of chemicals. It was shown that long-term chemical load in the crisis zone of the Aral Sea region causes a deviation of protein metabolism. The results obtained indicate a significant percentage of people with metabolic stress in the process of adaptation to high chemical load.